Prevalence and Antimicrobial Resistance Pattern of Acinetobacter baumannii in the Orthopedic Surgery Department of Imam Hussein Hospital from 2021 to 2024 - Haghighi, Mehrdad; Nayebi, Farbod (Novelty in Biomedicine, 2025)
Background: Nosocomial infections caused by Acinetobacter baumannii in orthopedic patients represent a growing challenge due to their prevalence, environmental persistence, and high levels of antimicrobial resistance. The increasing prevalence of resistant strains emphasizes the urgent need to improve infection control measures, antimicrobial surveillance, and develop new therapeutic options. This study aimed to determine the prevalence of nosocomial infection caused by Acinetobacter baumannii and its antibiotic resistance status in patients in the orthopedic ward of Imam Hussein Hospital from 2021 to 2024. Materials and Methods: Bacterial samples from orthopedic surgery patients at Imam Hussein Hospital were collected, stored at -20°C, and re-cultured on blood agar and selective media to ensure purity and accurate identification. Acinetobacter baumannii was confirmed using colony morphology, staining, Triple sugar Iron agar (TSI), and oxidase tests. Antibiotic resistance to imipenem, meropenem, and other antibiotics was assessed via disk diffusion, with colistin MIC determined per CLSI guidelines. Data were analyzed using SPSS version 22. Results: Of the 680 samples, 45 cultures were positive for Acinetobacter. All 45 Acinetobacter strains tested showed complete susceptibility to colistin. Among other antibiotics, ampicillin-sulbactam was relatively more effective with 17.8% susceptibility. Acinetobacter strains were susceptible to amikacin and imipenem in only one case, and were resistant in 95.6% and 97.8% of cases, respectively. For gentamicin, only one out of 17 tests showed Intermediate susceptibility, and the rest were resistant. For meropenem, one out of 42 tests showed Intermediate susceptibility, and the rest showed complete resistance. All Acinetobacter strains were completely resistant to the antibiotics cefepime, cefotaxime, ceftazidime, ceftriaxone, ciprofloxacin, levofloxacin, piperacillin-tazobactam, and cotrimoxazole. For minocycline, complete susceptibility was observed in both cases. Tetracycline susceptibility was also evaluated in 38 strains, of which only three were sensitive and 35 were resistant. Conclusion: This study confirms the rising resistance of Acinetobacter baumannii to multiple antibiotics, including cephalosporins, carbapenems, tetracyclines, and ciprofloxacin, limiting treatment to colistin and ampicillin-sulbactam. Hospital-acquired infections pose significant health and economic burdens, necessitating vigilant monitoring of resistance patterns, optimized antibiotic use, and stringent preventive measures, such as hand hygiene and equipment sterilization, to mitigate their impact.